Correlation of serum bilirubin and transcutaneous bilirubin in newborns - Arunachalmath, Pavitra V. (International Journal of Contemporary Pediatrics, 2021)
Background: Hyperbilirubinemia is a very common entity in newborns. Screening all the babies for hyperbilirubinemia is must. Serum bilirubin is the standard method of checking the bilirubin in newborns. This is very cumbersome, invasive and time consuming method. Hence many newborns will be discharged without screening. Transcutaneous bilirubinometry would help us in making this task easy and safe. Hence the present study was planned. Methods: This is an institutional cross sectional study conducted in a tertiary care hospital for a period of 6 months. After a written informed consent from parents/ guardians and considering selection criteria, 500 newborns with clinical jaundice were included in study. Each newborn was examined, transcutaneous bilirubin checked at forehead and sternum and serum bilirubin was done at the same time. Data was statistically analyzed to see the correlation between TcB and TSB. Results: Out of 500 newborns, 316 were males, 184 were females and 475 were term gestation and 25 were preterm. Coefficient of correlation was 0.73 and 0.72 for total serum bilirubin versus forehead and sternum respectively which were statistically significant. Conclusions: Transcutaneous bilirubinometer readings closely correlate with that of serum bilirubin. Hence TcB can be used as a safer, economical and effective tool in screening newborns for hyperbilirubinemia.